A Study to Inform the Design of a National Multicentre Randomised Controlled Trial to Evaluate If Reducing Serum Phosphate to Normal Levels Improves Clinical Outcomes including Mortality, Cardiovascular Events, Bone Pain, or Fracture in Patients on Dialysis. (23rd August 2015) - Bhargava, Ramya; Kalra, Philip A.; Brenchley, Paul; Hurst, Helen; Hutchison, Alastair
Abstract : Background . Retrospective, observational studies link high phosphate with mortality in dialysis patients. This generates research hypotheses but does not establish "cause-and-effect." A large randomised controlled trial (RCT) of about 3000 patients randomised 50 : 50 to lower or higher phosphate ranges is required to answer the key question: does reducing phosphate levels improve clinical outcomes? Whether such a trial is technically possible is unknown; therefore, a study is necessary to inform the design and conduct of a future, definitive trial. Methodology . Dual centre prospective parallel group study: 100 dialysis patients randomized to lower (phosphate target 0.8 to 1.4 mmol/L) or higher range group (1.8 to 2.4 mmol/L). Non-calcium-containing phosphate binders and questionnaires will be used to achieve target phosphate. Primary endpoint: percentage successfully titrated to required range and percentage maintained in these groups over the maintenance period. Secondary endpoints: consent rate, drop-out rates, and cardiovascular events. Discussion . This study will inform design of a large definitive trial of the effect of phosphate on mortality and cardiovascular events in dialysis patients. If phosphate lowering improves outcomes, we would be reassured of the validity of this clinical practice. If, on the other hand, there is no improvement, a reassessment of resource allocation to therapies proven to improve outcomes will result. Trial Registration Number . This trial is registered with ISRCTN registration number ISRCTN24741445 .